Elizabeth Bowen and Eudora Welty: Selected Correspondence. Issue 1 (May 2021) - Hepburn, Allan
Abstract : Over her career, Elizabeth Bowen published ten novels, yet she left no comprehensive theory of the novel. This essay draws especially upon 'Notes on Writing a Novel' (1945), 'The Technique of the Novel' (1953), and 'Truth and Fiction' (1956), as well as opinions that Bowen expressed in her weekly book columns for The Tatler, to formulate her key perceptions of, and rules for, writing a novel. Bowen defined her ideas by drawing upon the empirical evidence of novels by Elizabeth Taylor, Olivia Manning, H.E. Bates, Jane Austen, Gustave Flaubert, and numerous others. She gave particular thought to 'situation', by which she means the central problematic or the crux of the story. The situation precedes and fuels plot. The Second World War, Bowen claimed in her essays and reviews, had a decisive influence on heroism and contemporary fiction by heightening its scale and its repertory of situations.